New horizons for the Panhellenic Symposium of Oceanography & Fisheries - ARVANITIDIS, CHRISTOS; GEROVASILEIOU, VASILIS; KARACHLE, PARASKEVI K.; ZENETOS, ARGYRO (Mediterranean Marine Science, 2019)
The Panhellenic Symposium of Oceanography and Fisheries was firstly launched in Athens, 35 years ago sparked by the enthusiasm of the Greek aquatic scientists, massively supported by the voluntary contribution of the Hellenic Centre for Marine Research (HCMR) employees. Over the last three decades, the Symposium established and flourished as the forum for a wide range of marine and freshwater disciplines in the country. It became a tradition to a large audience since it has attracted researchers, academicians, students, entrepreneurs and the industry both from Greece and adjacent countries. The initial enthusiasm and support is growing with the inclusion of Universities and other educational/research institutes in the organization scheme. The “12th Panhellenic Symposium of Oceanography and Fisheries” 1 did not only deliver big changes in its operational mode but also opened new horizons to the scientific communities of Greece and adjacent areas. It has been a tipping point in this type of events in many aspects.